Cakil: Movement Creation Techniques in Pantomime Performing Arts - Welly Suryandoko (International Journal of Visual and Performing Arts, 2019)
Pantomime is the art of creating illusions by making the body a means of art communication. The body speaks and tells very emotionally; expressions are created through bodily movements. The movement brings silence to the wordless story. Pantomime also has many-body techniques and can be taken from any source. The purpose of this study is to make the Cakil movement technique in Javanese puppets. The Cakil movement is analyzed and used as a source of ideas of creation. These movements include Ngasak or Asakan, Ceklekan, Kelitan (ngelit), Ngancap. This technique is processed, and the results are used as a medium of expression in the art performance of mime. The results showed that the Cakil movement technique could produce new dynamic movements with strong character and be able to form a movement model that is based on the Cakil movement.